Point-of-Care Ultrasound Facilitates Management of Ruptured Ectopic Pregnancy. Issue 5 (May 2021) - Moake, Matthew M.; Price, Amanda B.; Titus, M. Olivia; Barnes, Ryan M.
Abstract : Abstract: Abdominal pain in the pregnant adolescent presents a diagnostic dilemma with potential life-threatening etiologies. We present a case where point-of-care ultrasound was used to facilitate diagnosis and expedite lifesaving management of a ruptured ectopic pregnancy. We further review the technique and literature for first-trimester transabdominal point-of-care ultrasound.